Generation of protonic acid sites from pentane on the surfaces of Pt/SO42--ZrO2 and Zn/H-ZSM5 evidenced by IR study of adsorbed pyridine - Triwahyono, Sugeng; Abdul Jalil, Aishah; Musthofa, Malik (Elsevier, 2010)
Pyridinium ion was formed from pyridine, which had been bound to Lewis acid sites on Pt/SO42--ZrO2 and Zn/H-ZSM5 by contact with pentane vapor. Protonic acid sites were generated on these surfaces by contact with pentane. The protonic acid sites generated in the presence of pentane were eliminated when pentane was removed from gas phase. The generation of the protonic acid sites occurred above 350 K for Pt/SO42--ZrO2 and above room temperature for Zn/H-ZSM5.